PERBANDINGAN PENGGUNAAN METODE COLLABORATIVE LEARNING DAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA KELAS VII SMP DARUL ARAFAH - Ira Vahlia (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
The aim of this research to analyze the essence of Junior high student learning outcomes Darul Arafah is still relatively low it is seen that the value of the student learning outcomes that achieve minimum completeness criteria (KKM) is still much below the passing standard, so it is still far from what is expected. From the analysis it can be concluded as follows: 1) There is a noticeable difference the average student learning outcomes are taught using methods of collaborative learning with an average of the learning outcomes of students who are taught with methods of discovery learning on the subject of integers students in grade 7 SMP Darul Arafah Sukajawa the school 2015/2016. 2) The average results learning collaborative learning method is lower than the average student learning outcomes are taught using methods of discovery learning on the subject of integers grade students grade 7 SMP Darul Arafah Sukajawa the school 2015/2016.